Hair Follicle Miniaturization in a Woolly Hair Nevus: A Novel "Root" Perspective for a Mosaic Hair Disorder. (March 2016) - Veraitch, Ophelia; Perez, Alfonso; Hoque, Shamali R.; Vizcay-Barrena, Gema; Fleck, Roland A.; Fenton, David A.; Stefanato, Catherine M.
Abstract : Abstract: Woolly hair nevus is a mosaic disorder characterized by unruly, tightly curled hair in a circumscribed area of the scalp. This condition may be associated with epidermal nevi. We describe an 11-year-old boy who initially presented with multiple patches of woolly hair and with epidermal nevi on his left cheek and back. He had no nail, teeth, eye, or cardiac abnormalities. Analysis of plucked hairs from patches of woolly hair showed twisting of the hair shaft and an abnormal hair cuticle. Histopathology of a woolly hair patch showed diffuse hair follicle miniaturization with increased vellus hairs.